(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study is to deal with community participation in dealing with the covid-19 outbreak to break the chain of covid-19 in the middle tombatu three village in response to the government regulation of Law No. 4 of 1984 as a guide for the community in the middle tombatu three village to work together in facing Covid-19 and to comply with government regulations so that not many people are affected by COVID-19 in the village of Tombatu Tiga Tengah and carry out the health protocols that have been regulated by the regional government. this research method is descriptive qualitative. The result of this research is that the Covid-19 handler analyst in the village of Tombatu Tiga is responding to the government regulation Law No. 4 of 1984 concerning infectious outbreaks. The results obtained are that the analysis of the participation in handling covid-19 in the village of Tombatu Tiga Tengah has been successfully carried out but there are still obstacles that occur such as many people who neglect to comply with health protocols and how much assistance has not been distributed to the community and there are still concessions that occur. in health protocols. Keywords : participation in handling Covid-19